Analisis Soal Ujian Akhir Semester Ganjil Mata Pelajaran Sejarah Indonesia Kelas XI Tahun Pelajaran 2019/2020 di Kota Padang - Silvia Desrijenatin; Zafri Zafri (Jurusan Sejarah FIS UNP, 2020)
This study aims to analyze the distribution of material, basic competencies, indicators of achievement of competencies that exist in the RPP, as well as the level of thinking in odd semester final exam questions for history subjects class XI 2019/2020 academic year. This research was conducted at Adabiah 2 Senior High School in Padang. This type of research is a qualitative research with descriptive methods. The object of this study is the odd semester final exam subject for history class XI. The data in this study were obtained by means of document studies. The results showed that: 1) The distribution of material and basic competencies in the questions were not evenly distributed, 2) The distribution of competency achievement indicators was not evenly distributed, 3) The distribution of thinking levels in odd semester final exam questions was not evenly distributed, questions were dominated by the level of thinking thinking (C1) and understand (C2), 4 The average level of thinking distribution in questions is at the C1 level as many as 35 questions and C2 as many as 5 questions, while the level of thinking C3, C4, C5, and C6 has no problems.